An innovative inverse analysis technique for building cooling design with HVAC systems. (2nd April 2016) - Moftakhari, Ardeshir; Aghanajafi, Cyrus; Ghazvin, Ardalan Moftakhari Chaei
Abstract : In the present study, a new thermal design approach is presented to simulate HVAC cooling systems inside buildings using a combination of direct cooling load modeling and inverse analysis technique. With the use of direct cooling load modeling, a sample building equipped with an HVAC cooling system is modeled using finite-volume scheme in order to calculate cooling load and temperature field inside the domain. Energy consumption of the building is computed using the building energy simulation algorithm. Then, the results of the indoor temperature field are used as input data for the inverse algorithm to estimate thermal design parameters in the building. To verify the accuracy of the present study, we compare the results of numerical developed code with Carrier and Energy-Plus software for direct energy modeling and then the results of inverse simulation are presented for the sample building.